2000
DOI: 10.1074/jbc.275.8.5947
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Basal and Cyclic AMP Response Elements in the Promoter of the Rat GTP Cyclohydrolase I Gene

Abstract: 5812 base pairs of rat GTP cyclohydrolase I (GTPCH) 5-flanking region were cloned and sequenced, and the transcription start site was determined for the gene in rat liver. Progressive deletion analysis using transient transfection assays of luciferase reporter constructs defined the core promoter as a highly conserved 142-base pair GC-rich sequence upstream from the cap site. DNase I footprint analysis of this region revealed (5 3 3) a Sp1/GC box, a noncanonical cAMP-response element (CRE), a CCAAT-box, and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(99 citation statements)
references
References 56 publications
2
97
0
Order By: Relevance
“…This intermediate is then converted to BH 4 in two subsequent reactions catalyzed by 6-pyruvoyltetrahydropterin synthase and sepiapterin reductase, respectively, neither of which are rate-limiting. The signal transduction pathways that regulate induction of GTPCH are not well understood, although transcription factors such as NF-␤ and AP-1 are required for GTPCH mRNA expression (10) and recently, 5.8 kb of the rat GTPCH promoter have been cloned and found to contain a number of potential cytokine responsive elements (11). Although it is well established that iNOS induction is dependent on the redox-sensitive transcription factor NF-B, we previously showed that NF-␤ was not required for induction of GTPCH in rat C6 glioma cells, a convenient astrocyte model, when stimulated with combinations of proinflammatory cytokines (12).…”
Section: (R)-5678-tetrahydrobiopterin (Bh 4 )mentioning
confidence: 99%
“…This intermediate is then converted to BH 4 in two subsequent reactions catalyzed by 6-pyruvoyltetrahydropterin synthase and sepiapterin reductase, respectively, neither of which are rate-limiting. The signal transduction pathways that regulate induction of GTPCH are not well understood, although transcription factors such as NF-␤ and AP-1 are required for GTPCH mRNA expression (10) and recently, 5.8 kb of the rat GTPCH promoter have been cloned and found to contain a number of potential cytokine responsive elements (11). Although it is well established that iNOS induction is dependent on the redox-sensitive transcription factor NF-B, we previously showed that NF-␤ was not required for induction of GTPCH in rat C6 glioma cells, a convenient astrocyte model, when stimulated with combinations of proinflammatory cytokines (12).…”
Section: (R)-5678-tetrahydrobiopterin (Bh 4 )mentioning
confidence: 99%
“…In our previous study, we showed increased promoter activity of the GCH gene in the V-1 clones (52) as we did for that of the TH gene in this report. Recently, ϳ150 bp of the 5Ј-promoter region of the GCH gene was identified as the region contributing to basal and cyclic AMP-induced transcriptional activity and containing a non-canonical CRE (28,53), and we showed that this region was sufficient for the increased activity of the GCH promoter in the V-1 clones (52). Hirayama et al (53) reported that the proximal promoter region could recruit ATF-2.…”
Section: Discussionmentioning
confidence: 99%
“…A labeled probe (50,000 cpm) was then used in EMSA as previously described (19). Briefly, the probe was incubated with or without 1 to 10 g whole cell extracts at 4°C for 20 min in a reaction mixture that contained 12.5 mM HEPES, pH 7.9, 100 mM KCl, 1 mM EDTA, 1 mM DTT, 1 g poly dI-dC, and 10% glycerol.…”
Section: Methodsmentioning
confidence: 99%